Ethanol Iris tenuifolia extract reduces brain damage in a mouse model of cerebral ischaemia. (23rd November 2017) - Jalsrai, Aldarmaa; Reinhold, Annegret; Becker, Axel
Abstract : In the previous experiments, the neuroprotective role of Iris tenuifolia Pall. (IT) in the model of middle cerebral artery occlusion (MCAO) was investigated. In addition, the concentrations of the cytokines tumour necrosis factor‐alpha and interleukin‐6 in blood plasma were measured. It was found that IT administered 1 hr prior to MCAO or immediately after MCAO reduced infarct volume significantly. IT application 1 and 4 hr after MCAO, respectively, was without any effect on infarct volume. There were no significant changes as regards tumour necrosis factor‐alpha, whereas interleukin‐6 concentrations were increased in blood plasma. This is the first evidence that flavonoids from Iris tenuifolia exert protective effects in the in vivo MCAO model. Our results suggest that these flavonoids are likely to be beneficial to humans by virtue of their ability to reduce infarct volume.